Synthesis and Biological Evaluation of Novel Carbazole Hybrids as Promising Antimicrobial Agents. Issue 5 (15th April 2020) - Shaikh, Mahamadhanif S.; Chandrasekaran, Balakumar; Palkar, Mahesh B.; Kanhed, Ashish M.; Kajee, Afsana; Mlisana, Koleka P.; Singh, Parvesh; Ghai, Meenu; Cleopus Mahlalela, Mavela; Karpoormath, Rajshekhar
Abstract: Two series of carbazole analogs of 8‐methoxy‐ N ‐substituted‐9 H ‐carbazole‐3‐carboxamides (series 1) and carbazolyl substituted rhodanines (series 2) were synthesized through facile synthetic routes. All the final compounds from these two series were evaluated for their preliminary in vitro antifungal and antibacterial activity against four fungal ( Candida albicans, Cryptococcus neoformans, Cryptococcus tropicalis and Aspergillus niger ) and four bacterial ( Staphylococcus aureus, Bacillus subtilis, Escherichia coli and Pseudomonas aeruginosa ) strains, respectively. Among the tested compounds, three compounds of series 1 displayed promising antifungal and antibacterial activity, especially against C. neoformans and S. aureus . In addition, one compound of series 1 displayed notable antimicrobial activity (MIC: 6.25 μg/mL) against clinical isolates of C. albicans and C. neoformans (MIC: 12.5 μg/mL). From the second series, four compounds exhibited significant antifungal and antibacterial activity, especially against C. neoformans and S. aureus . The most active compound of series 2 displayed a prominent antimicrobial activity against C. neoformans (MIC: 3.125 μg/mL) and S. aureus (MIC: 1.56 μg/mL), respectively. Abstract :